(untitled) (Research, Society and Development, 2022)
An especially important species in South America, yerba mate (Ilex paraguariensis A.St.-Hil) is traditionally consumed as tea, chimarrão and tererê. Due to the formation of mate plantations with low productivity and high heterogeneity, genetic improvement actions have been conducted as a way to generate more productive cultivars of this species. In this sense, the present study aimed to estimate phenotypic and genetic parameters of yerba mate production traits earlier in provenance and progeny tests, implanted in the municipalities of Chapecó and Guatambu, in the western region of Santa Catarina State (South America). In each environment, 55 open pollinated yerba mate progenies were evaluated in a randomized complete block design, with five replications and three plants per plot. The traits measured at two years old were: height and crown diameter (m) and at three years were: visually estimated commercial biomass, weighed commercial biomass and thick branch mass (kg). The data obtained was analyzed using the genetic-statistical Selegen software. The results obtained support that there is genetic variability in the open pollinated yerba mate progenies evaluated in Santa Catarina, with possible gains by selecting the best parent trees for future production of improved seeds and for cloning.